2006
DOI: 10.1086/502641
|View full text |Cite
|
Sign up to set email alerts
|

Spectral States of the X‐Ray Binary IGR J17091−3624 Observed byINTEGRALandRXTE

Abstract: IGR J17091-3624 was discovered in 2003 April by INTEGRAL/IBIS during its Galactic Centre Deep Exposure programme. The source was initially detectable only in the 40-100 keV range, but after two days was also detected in the 15-40 keV range. Its flux had by then increased to 40 mCrab and 25 mCrab in the 15-40 keV and 40-100 keV bands respectively. RXTE observed the source simultaneously on 2003 April 20, with an effective exposure of 2 ksec. We report here the spectral and temporal evolution of the source, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…It exhibits a large variability in X-rays, and it is uncertain if this source is a Be/X-ray binary or an LMXB. Capitanio et al (2006) confirm the low absorption (N H ≤ 1 × 10 22 cm −2 ) and Comptonised spectrum of this source. Negueruela & Schurch (2007) proposed the 2MASS J17090199-3623260 source as a candidate counterpart, based on photometric catalogues.…”
Section: Igr J17091-3624supporting
confidence: 80%
“…It exhibits a large variability in X-rays, and it is uncertain if this source is a Be/X-ray binary or an LMXB. Capitanio et al (2006) confirm the low absorption (N H ≤ 1 × 10 22 cm −2 ) and Comptonised spectrum of this source. Negueruela & Schurch (2007) proposed the 2MASS J17090199-3623260 source as a candidate counterpart, based on photometric catalogues.…”
Section: Igr J17091-3624supporting
confidence: 80%
“…Nevertheless, a previous work by Parmar et al (2003) reported three observations Table 1) were taken at the end of July 2004 and suggest that the source was then still in the high, soft state, while the optical observation #7 was carried out one day after this last radio detection, with the source transiting to a harder state. INTEGRAL data covered the final part of the outburst and showed that the source, which seemed to harden after the peak of the emission, suddenly fell to a softer state (Capitanio et al 2006). Our observations #8 and #9 correspond to this high, soft state.…”
Section: The 2003 Outburst (I)mentioning
confidence: 99%
“…According to Capitanio et al (2006), the source has not been active since 2004. Perhaps the JHK observations were made at a time when the source was active and the colours dominated by an accretion disk, mimicking the flat IR spectrum of an early type star.…”
Section: Igr J17091-3624mentioning
confidence: 99%